NUTRIENT UPTAKE AND YIELD OF RICE AS INFLUENCED BY DIFFERENT SYSTEMS OF RICE CULTIVATION AND ORGANIC NUTRIENT MANAGEMENT PRACTICES - K. VINEELA (The Journal of Research ANGRAU, 2024)
The field experiment was conducted during late Kharif season of 2021-22 and 2022-23 in splitplot design and replicated thrice to record the nutrient uptake and grain yield as influenced by different organic nutrient management practices under different systems of rice cultivation. Among the different systems of rice cultivation, significantly higher dry matter production, nutrient uptake and yield were noticed under normal transplanted rice which was at par with wet direct seeded rice. Among the organic nutrient management practices tested, significantly higher nutrient uptake as well as yield were obtained with the application of 100% RDN (Recommended Dose of Nitrogen) through poultry manure which was at par with 50% RDN through VC + 50% RDN through poultry manure but both of them were significantly inferior to 100% RDN (120-60-40 kg N, P2O5, K2O ha-1) through inorganic fertilizers on sandy clay loam soils of Southern Agro-Climatic Zone of Andhra Pradesh. Application of 100% RDN through Poultry Manure in transplanted rice was found effective in obtaining higher nutrient uptake and yield than rest of the systems of rice cultivation and organic nitrogen management practices.